1994
DOI: 10.1002/gcc.2870100203
|View full text |Cite
|
Sign up to set email alerts
|

Complex composition and co‐amplification of SAS and MDM2 in ring and giant rod marker chromosomes in well‐differentiated liposarcoma

Abstract: Extra abnormal chromosomes (rings and giant rods) containing chromosome 12 sequences are characteristic of well-differentiated liposarcoma (WDLPS). By whole chromosome painting we found in 6 WDLPS that minimally 5 chromosomes had contributed to the formation of the extra abnormal chromosomes. To the constant chromosome 12 contribution, sequences were variably added from chromosomes 1, 4, and 16. Material from chromosomes 1, 4, and 12 was identified by painting in interphase nuclear projections ("blebs") and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
114
1
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(127 citation statements)
references
References 28 publications
9
114
1
3
Order By: Relevance
“…24 MDM2, a negative regulator of p53 was amplified in one of our phyllodes tumors cases. MDM2 is found to be frequently amplified in some sarcomas such as osteosarcomas, 46 liposarcomas, 47,48 'socalled' malignant histocytofibromas, 39,43 leiomyosarcomas 43 and neuroglial tumors. 49 The fact that in our This study has provided evidence that borderline and malignant phyllodes tumors could not be differentiated on the basis of the presence and of the number of chromosomal imbalances.…”
Section: Discussionmentioning
confidence: 99%
“…24 MDM2, a negative regulator of p53 was amplified in one of our phyllodes tumors cases. MDM2 is found to be frequently amplified in some sarcomas such as osteosarcomas, 46 liposarcomas, 47,48 'socalled' malignant histocytofibromas, 39,43 leiomyosarcomas 43 and neuroglial tumors. 49 The fact that in our This study has provided evidence that borderline and malignant phyllodes tumors could not be differentiated on the basis of the presence and of the number of chromosomal imbalances.…”
Section: Discussionmentioning
confidence: 99%
“…WDLS are characterized by supernumerary abnormal chromosomes (rings or giant rod markers) containing sequences from the q13 ± 15 segment of chromosome 12 (Dal Cin et al, 1993). We have previously shown that MDM2, but not CDK4, is consistently included in amplicons in WDLS (Pedeutour et al, 1994). Sequences from several chromosomes contribute to these markers, making the generation of`secondary translocations' or of novel fusion genes within the markers likely.…”
Section: Discussionmentioning
confidence: 99%
“…in other soft tissue tum ors, double m inutes, ring chrom osom es, an d large rod-shaped m arkers have repeatedly been en co u n tered. These latter anom alies appear to be associated w ith gene am plifications [6][7][8]. Also, osteosarcom as originate from supportive tissues [9].…”
Section: Introductionmentioning
confidence: 99%